A construção da autonomia numa perspectiva piagetiana: contribuições para a Educação Infantil - Silva, Priscila Pelarin da [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
This paper aims at discussion the construction of autonomy of cognitive development and child morality, according to the Piagetian approach view of the influence of socio-moral classroom in kindergarten. It is known that education is a very important part of participation in relation to the development of autonomy by the child, especially when it comes to kindergarten who becomes responsible for performing the initial encouragement of this ability, respecting the phase cognitive development in which the child is. We focus, therefore, the need for education and teaching activities that enable this construction offering little opportunity to exercise and build their first signs of autonomy. For their achievement, in addition to literature, which has been supported by theoretical studies of Jean Piaget, we chose a field research where we look, from the interview and observation, investigate the socio-moral environment of a room class of a school Kindergarten, highlighting the important opportunities for the exercise of autonomy for the children, amid the routine of the group. The interview was focused on the pursuit of basic knowledge of the educator on the subject, as well as what would be aware of the role of preschool in the process of moral development and about their own role as an educator this mode of education. Since the remark was directed at the teacher's procedures against the encouragement of social and moral ability, focusing mainly on interpersonal relationships in the classroom. Our classroom has proved to be a cooperative environment and therefore we emphasize the importance of the teacher's conduct that permeated the day-to-day classroom and encouraged to start building this skill by the student. The main objective of this study therefore was to investigate the possibilities and outcomes that have a school experience for the development of autonomy for children

O presente trabalho objetiva abordar a construção da autonomia no processo de desenvolvimento cognitivo e moral infantil, de acordo com a perspectiva piagetiana, tendo em vista a influência do ambiente sócio-moral da sala de aula na Educação Infantil. Sabe-se que a educação escolar tem uma parcela de participação bastante relevante no que se refere ao desenvolvimento da autonomia pela criança, principalmente quando se trata da Educação Infantil que se torna responsável por realizar os primeiros encorajamentos desta habilidade. Neste processo enfocamos, pois, a necessidade de uma Educação e Pedagogia ativas que possibilitem esta construção oferecendo aos pequenos oportunidades de exercerem e construírem seus primeiros indícios da autonomia. Para isso, além da pesquisa bibliográfica, que teve como suporte teórico os estudos de Jean Piaget, optamos por uma pesquisa de campo em que procuramos, a partir da técnica da entrevista e da observação, investigar o ambiente sócio-moral de uma sala de aula de uma Escola de Educação Infantil, destacando as oportunidades relevantes de exercício da “autonomia” pelas crianças, em meio à rotina do grupo. A entrevista esteve voltada para a busca dos conhecimentos básicos da educadora sobre o tema, bem como qual seria consciência quanto ao papel da pré-escola neste processo de desenvolvimento moral e sobre o seu próprio papel enquanto educadora desta modalidade de ensino. Já a observação esteve direcionada para os procedimentos da professora frente o encorajamento desta habilidade sócio-moral que, tendo como foco principal as relações interpessoais na sala de aula. Nossa sala de aula mostrou ser um ambiente cooperativo e, por isso, pudemos enfatizar a importância das condutas da professora que permearam o dia-a-dia da turma e que encorajaram a construção inicial desta habilidade pelo aluno. O objetivo principal deste trabalho, portanto, foi investigar as possibilidades
Keywords: Piaget, Jean, 1896-1980; Educação de crianças; Desenvolvimento cognitivo; Education and child; Cognitive development and socio-moral; Socio-moral environment